Rethinking Differentiated Mathematics Instruction: Teachers’ Readiness and Instructional Challenges in Elementary Schools - Komang Sujendra Diputra; I Putu Julianto; Ni Ketut Desia Tristiantari; Gusti Ayu Putu Sukma Trisna; Khabibur Rohman (UIN Siber Syekh Nurjati Cirebon, 2026)
Background: Differentiated instruction has become increasingly important in addressing students’ diverse learning needs, particularly in elementary mathematics classrooms characterized by varying levels of numeracy readiness and learning abilities. Previous studies have rarely examined teachers’ pedagogical readiness and implementation challenges simultaneously, although both may shape whether conceptual understanding translates into adaptive classroom practice. Aims: This study aims to analyze teachers’ readiness and instructional challenges in differentiated mathematics instruction within elementary school contexts, as well as the relationship between them. Methods: This study employed a mixed methods approach involving elementary school teachers in Bali Province, Indonesia. Quantitative data were analyzed using descriptive statistics and Pearson’s correlation analysis, while qualitative data from open-ended responses were analyzed using thematic analysis. Results: The findings indicated that teachers’ readiness was generally at a moderate level. Conceptual readiness obtained the highest mean score, whereas assessment readiness showed the lowest level among the readiness dimensions. Classroom heterogeneity challenges emerged as the most dominant instructional challenge. The study also revealed a significant negative relationship between teachers’ readiness and instructional challenges. Thematic findings further showed that teachers experienced difficulties in managing diverse mathematical abilities, conducting differentiated assessment, and implementing adaptive instruction within limited instructional time. Conclusions: Differentiated mathematics instruction requires not only conceptual understanding but also stronger pedagogical readiness and institutional support to foster more adaptive mathematics learning practices in elementary schools. Examining readiness and challenges together clarifies the factors shaping its implementation in elementary schools.